2011
DOI: 10.1007/s00330-011-2111-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enlarged mediastinal lymph nodes in heavy smokers—a comparative study

Abstract: The present study demonstrates that enlarged mediastinal lymph nodes may occur in a rather high percentage of heavy smokers, especially in those with a MDCT finding of severe bronchitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Non-specific signs such as fever, weight loss, and decreased energy are shared by common IMHL differentials such as sarcoidosis, tuberculosis, lymphoma, and malignant carcinoma. Adding to the diagnostic dilemma, reactive lymphocytosis is associated with prevalent chronic diseases such as chronic obstructive lung disease [1], interstitial lung disease [2], and congestive heart failure [3,4]. Therefore, patients with IMHL often require an invasive procedure to obtain tissue for cytohistologic and microbiologic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Non-specific signs such as fever, weight loss, and decreased energy are shared by common IMHL differentials such as sarcoidosis, tuberculosis, lymphoma, and malignant carcinoma. Adding to the diagnostic dilemma, reactive lymphocytosis is associated with prevalent chronic diseases such as chronic obstructive lung disease [1], interstitial lung disease [2], and congestive heart failure [3,4]. Therefore, patients with IMHL often require an invasive procedure to obtain tissue for cytohistologic and microbiologic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Anthracosis is a form of pneumoconiosis which is not only caused by coal dust but also other environmental factors such as air pollution, biomass fuels used extensively for cooking ("hut lung"), and cigarette smoking [9,[16][17][18][19] . A recently published comparative study on 44 heavy smokers and 44 non-smokers demonstrated that enlarged mediastinal lymph nodes may occur in up to 52% of heavy smokers, especially in those with severe bronchitis [9] .…”
Section: Discussionmentioning
confidence: 99%
“…A recently published comparative study on 44 heavy smokers and 44 non-smokers demonstrated that enlarged mediastinal lymph nodes may occur in up to 52% of heavy smokers, especially in those with severe bronchitis [9] . The authors of that study assumed that lymph node enlargement in smokers may be caused by a deposition of anthracotic material and dust induced response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is characterised by formation of black nodules on the bronchioles, focal emphysema, and the deposition of coal dust in lymph nodes ( Figure 1). 2 Since anthracosis is a form of pneumoconiosis not only caused by the occupational exposure to coal dust (coal workers pneumoconiosis), but also by cigarette smoking and environmental pollution, 3 radiologists should be aware of mediastinal lymph node enlargement occurring in these conditions, as this fact may impact staging of malignant lung diseases per se. To our knowledge, computed tomography (CT) appearance of histologically proven lymph node anthracosis has not been substantially addressed in the literature so far.…”
Section: Introductionmentioning
confidence: 99%